EMERGING TRENDS IN FINTECH: HOW TECHNOLOGY IS RESHAPING THE GLOBAL FINANCIAL LANDSCAPE - Ramakrishna Ramadugu; Laxman doddipatla (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Background: Financial technology (fintech) has evolved rapidly, changing the global financial landscape consumer behavior, and institutional operations. This study looks at the adoption of key fintech technologies like blockchain, artificial intelligence (AI), and mobile payments, based on trends before 2021.Methods: The approach was mixed methods, using quantitative data from surveys of 150 fintech stakeholders across North America, Europe, and Asia, and qualitative insights from literature reviews of industry reports and financial data from 2015 to 2020.Results and Discussion: The research shows that mobile payment systems are adopted by 78% of people, mostly in Asia, and North America leading to AI usage at 62%. Overall, fintech adoption led to an average 15% revenue growth for firms, a 20% increase in customer retention, and a 17% decrease in fraud-related losses. Regulatory compliance and consumer trust were the biggest challenges for 62% and 30% of respondents, respectively. The study also shows regional differences in fintech adoption strategies, and that institutions need to address regulatory complexities and build consumer confidence to promote wider adoption.Conclusion: With the further evolution of fintech technologies, those in financial institutions need to understand what will influence the adoption of these technologies, and address identified challenges in this study, to effectively leverage these innovations. More research continues to be needed to further study the long-term effects of fintech on financial stability and consumer conduct.